Enhancing human thermal comfort in hot arid cities: A systematic review of urban heat island observations and mitigation strategies - Omer Abedrabboh (17346847) (2025)
The urban heat island (UHI) effect significantly impacts cities' thermal environments, especially in hot arid regions (Köppen-Geiger: BWh), where rapid urbanization has intensified heat stress. These areas, characterized by extreme heat and drought, face increased outdoor thermal discomfort and high energy demands for cooling. This study reviews recent observations of the UHI phenomenon, focusing on climate variations across urban forms (local climate zones) and the effectiveness of mitigation strategies in hot arid cities. Key findings include: (1) majority of hot arid cities experience a daytime urban cool island effect, (2) urbanization (land use/land cover changes) led to lower daytime and higher nighttime temperatures, (3) during the day, bare sand and industrial zones (LCZs F, 8, 10) record the highest temperatures, while compact built areas (LCZs 1, 2, 3) are hottest at night, (4) green infrastructure (mostly modelled and simulated using ENVI-met (local/micro-scale) and Weather Research and Forecasting Tool (mesoscale)), particularly tree canopies, is the most implemented and effective heat mitigation strategy, followed by cool materials, and (5) coastal arid cities show moderated UHI intensity. This review highlights the importance of targeted strategies to reduce UHI effects, enhance thermal comfort, and lower buildings’ cooling energy consumption in hot arid cities. Other Information Published in: Building and Environment License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.buildenv.2025.113398